2022
DOI: 10.1093/glycob/cwac070
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of a new class of O-linking oligosaccharyltransferases from the Moraxellaceae family

Abstract: Bacterial protein glycosylation is commonly mediated by oligosaccharyltransferases (OTases) that transfer oligosaccharides en bloc from preassembled lipid-linked precursors to acceptor proteins. Natively, O-linking OTases usually transfer a single repeat unit of the O-antigen or capsular polysaccharide to the side chains of serine or threonine on acceptor proteins. Three major families of bacterial O-linking OTases have been described: PglL, PglS, and TfpO. TfpO is limited to transferring short oligosaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Since the identification of bacterial glycosylation more than two decades ago, a range of discrete bacterial glycosylation systems have been identified responsible for the modification of specific proteins, such as flagella or pilin, as well as general glycosylation systems responsible for the modification of multiple proteins. , Within known glycosylation pathways, several classes of oligosaccharyltransferases have been identified which enable the en bloc transfer of complex glycans onto proteins from lipid-linked oligosaccharides within the periplasm of Gram-negative species. ,, Of the identified oligosaccharyltransferases, the Pilin-glycosylation ligases, also known as the PglL family of enzymes, , are now recognized to be widely distributed within Gram-negative genera and responsible for O -linked glycosylation across a range of species. ,, Across the known PglL glycosylation systems, differences in the proteins ,, and amino acid residues , were able to be modified as well as the compositions , and lengths ,, of glycans were able to be effectively transferred have now been observed supporting extensive diversity in PglL functionality. Consistent with this across the Moraxellaceae , which contains the Acinetobacter genera, divergent Moraxellaceae PglL homologues are now known to possess unique glycosylation targeting specificities . Due to the diversity within the PglL enzymes of the Moraxellaceae understanding the substrates of glycosylation is critical to dissecting the roles of these systems especially within poorly understood species such as the human pathogen Acinetobacter baumannii .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Since the identification of bacterial glycosylation more than two decades ago, a range of discrete bacterial glycosylation systems have been identified responsible for the modification of specific proteins, such as flagella or pilin, as well as general glycosylation systems responsible for the modification of multiple proteins. , Within known glycosylation pathways, several classes of oligosaccharyltransferases have been identified which enable the en bloc transfer of complex glycans onto proteins from lipid-linked oligosaccharides within the periplasm of Gram-negative species. ,, Of the identified oligosaccharyltransferases, the Pilin-glycosylation ligases, also known as the PglL family of enzymes, , are now recognized to be widely distributed within Gram-negative genera and responsible for O -linked glycosylation across a range of species. ,, Across the known PglL glycosylation systems, differences in the proteins ,, and amino acid residues , were able to be modified as well as the compositions , and lengths ,, of glycans were able to be effectively transferred have now been observed supporting extensive diversity in PglL functionality. Consistent with this across the Moraxellaceae , which contains the Acinetobacter genera, divergent Moraxellaceae PglL homologues are now known to possess unique glycosylation targeting specificities . Due to the diversity within the PglL enzymes of the Moraxellaceae understanding the substrates of glycosylation is critical to dissecting the roles of these systems especially within poorly understood species such as the human pathogen Acinetobacter baumannii .…”
Section: Introductionmentioning
confidence: 88%
“…Consistent with this across the Moraxellaceae, which contains the Acinetobacter genera, divergent Moraxellaceae PglL homologues are now known to possess unique glycosylation targeting specificities. 37 Due to the diversity within the PglL enzymes of the Moraxellaceae understanding the substrates of glycosylation is critical to dissecting the roles of these systems especially within poorly understood species such as the human pathogen Acinetobacter baumannii. A. baumannii is an opportunistic pathogen associated with nosocomial infections including ventilator-associated pneumonia, urinary tract, and wound infections.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24−26 While early studies sought to confirm the activity of PglL enzymes using heterogeneous expression systems 27−29 or proteomic approaches, 15,24,30,31 recent studies have focused on expanding our understanding of their enzymatic capacities. These recent studies have demonstrated that PglL oligosacchar-yltransferases can possess unique targeting ranges 32−34 as well as diverse glycan tolerances, 35,36 yet little insights have been gained about the functional roles of these glycosylation systems within the bacterial species that possess them or the conserved properties of these enzymes across genera.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The PglL enzymes represent one of the largest families of oligosaccharyltransferases and have been confirmed to mediate O-linked glycosylation across a range of bacteria including Acinetobacter, , Francisella, Pseudomonas, Neisseria, Ralstonia, and Burkholderia species. While early studies sought to confirm the activity of PglL enzymes using heterogeneous expression systems or proteomic approaches, ,,, recent studies have focused on expanding our understanding of their enzymatic capacities. These recent studies have demonstrated that PglL oligosaccharyltransferases can possess unique targeting ranges as well as diverse glycan tolerances, , yet little insights have been gained about the functional roles of these glycosylation systems within the bacterial species that possess them or the conserved properties of these enzymes across genera.…”
Section: Introductionmentioning
confidence: 99%